2020
DOI: 10.1136/oemed-2020-106866
|View full text |Cite
|
Sign up to set email alerts
|

Household transmission and incidence of positive SARS-CoV-2 RT-PCR in symptomatic healthcare workers, clinical course and outcome: a French hospital experience

Abstract: ObjectivesAlthough healthcare workers (HCWs) have been particularly affected by SARS-CoV-2, detailed data remain scarce. In this study, we investigated infection rates, clinical characteristics, occupational exposure and household transmission among all symptomatic HCWs screened by SARS-CoV-2 RT-PCR between 17 March (French lockdown) and 20 April.MethodsSARS-CoV-2 RT-PCR was proposed to symptomatic (new cough or dyspnoea) HCWs at Creteil Hospital in one of the Parisian suburbs most severely affected by COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
34
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 25 publications
5
34
0
3
Order By: Relevance
“…This strategy produced proportions [ 13 ] instead of crude rates. The results confirm the relevance of HCWs’ exposure to infection risk [ 1 , 2 , 3 , 4 , 6 , 11 , 30 , 35 , 37 , 41 ]. We avoided producing localized results by studying a state in each region of the country.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This strategy produced proportions [ 13 ] instead of crude rates. The results confirm the relevance of HCWs’ exposure to infection risk [ 1 , 2 , 3 , 4 , 6 , 11 , 30 , 35 , 37 , 41 ]. We avoided producing localized results by studying a state in each region of the country.…”
Section: Discussionsupporting
confidence: 74%
“…A relevant result to highlight is that professionals performing tasks that, in theory, do not require dealing directly with patients occupied the second position in the number of affected. In France, the incidence rate of symptomatic COVID-19 infection also varied when comparing occupational subgroups [ 35 ]. However, some controversies are observed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Re-exposure to more COVID-19 carriers or contaminated physical services [ 17 ] may have contributed to an increased level of the contracted viral load, which may have expedited the symptomatic state. Nevertheless, this observation does not undermine the role of household transmission among retired or unemployed people [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The original rapid review included 34 studies on risk factors for coronavirus infections (3 studies on SARS-CoV-2 infection, 29 studies on SARS-CoV-1 infection, and 2 studies on Middle East respiratory syndrome–CoV infection) ( 1 ); 46 studies (44 studies on SARS-CoV-2 infection, 0 studies on SARS-CoV-1 infection, and 2 studies on Middle East respiratory syndrome–CoV infection) were added in prior updates ( 2 , 21–25 ). For this update, 12 cohort studies ( 3–9 , 11 , 14 , 15 , 18 , 19 ) and 6 cross-sectional studies ( 10 , 12 , 13 , 16 , 17 , 20 ) were added ( Supplement Table 1 ). Four studies were done in the United States ( 4 , 7 , 18 , 20 ), 10 in Europe (Spain [ 5 , 11 , 14 ], Italy [ 8 , 9 ], the United Kingdom [ 12 , 17 ], France [ 13 ], Sweden [ 15 ], and the Netherlands [ 15 ]), 2 in India ( 6 , 10 ), and 1 each in China ( 19 ) and Egypt ( 3 ).…”
mentioning
confidence: 99%
“…Nine new studies reported inconsistent associations between direct patient contact or contact with patients with COVID-19 and risk for SARS-CoV-2 infection or seropositivity primarily based on unadjusted risk estimates ( 3–5 , 7 , 8 , 10 , 14 , 18 , 19 ). In 2 studies that controlled for potential confounders, direct contact with patients with COVID-19 was associated with increased risk for infection versus no contact (adjusted OR, 1.69 [CI, 1.28 to 2.24]) ( 14 ) and versus a nonclinical health care worker role (adjusted OR, 3.08 [CI, 1.09 to 8.78]) ( 13 ).…”
mentioning
confidence: 99%